PEMANFAATAN POTENSI GANGGANG HIJAU (Ulva lactuca) SEBAGAI ANTIOKSIDAN ALAMI PADA PENCEGAHAN INFARK MIOKARD AKUT - Mahmud, Iwan; Pertiwi, Reza; Azis, Nofa Risma; Reviana, Desi Novita (Program Kreativitas Mahasiswa - Penelitian, 2014)
Acute myocardial infarction is a myocardial necrosis due to blood flow to the heart muscle is disrupted. The occurrence of acute myocardial infarction is usually due to atherosclerosis of coronary arteries. Acute myocardial necrosis caused by total blockage of a coronary artery by a thrombus formed on an unstable atherosclerotic plaque. Radical compounds can cause auto-oxidation reaction that can cause lipid peroxidation which resulted in the accumulation of lipids in the artery walls and cause atherosclerosis are at great risk. Antioxidant compounds capable of capturing free radicals caused by auto-oxidation reaction that can cause lipid peroxidation which resulted in the accumulation of lipids in the artery walls and cause atherosclerosis are at great risk. Melatonin and sulfate content of polysaccharides present in Ulva lactuca.L have antioxidant activity according to several studies that have been done. This research method is done in 2 ways, namely in vitro and in vivo. This in vitro test using qualitative and quantitative tests using DPPH reagent. As for the in vivo test is used to measure the levels of MDA (malonaldehyde). Extracts of green algae (Ulva lactuca L.) has the ability of antioxidants seen from in vitro assays and in vivo. Data percent DPPH radical scavenging (ES50) on average positive control gallic acid and ethanol extracts of green algae (Ulva lactuca L.) respectively, are 0.912 ug / ml and 1426.616 pg / ml. The analysis showed that Â 200 mg / kg is an ideal dosage to prevent acute myocardial infarction.Keywords: Â Green algae, myocardial infarction, heart, aterosclerosis